Chronic granulomatous disease/Idiopathic aseptic facial granuloma. - Garofalo, L.; Bonifazi, E. (European Journal of Pediatric Dermatology, 2014)
Chronic granulomatous disease (CGD) is a primary immunodeficiency caused by a NADPH (nicotinamide-adenine-dinucleotide-phosphate) oxidase enzyme defect and characterized by recurrent bacterial and fungal infections due to the inability to kill the phagocytized microbes and thus associated with cell-mediated responses and granuloma formation. Initially the skin lesions of CGD are not easily differentiated clinically from idiopathic aseptic facial granuloma, which is a benign self-healing disease.